Comoros : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2001)
This recent economic developments report (RED) provides background information on economic developments in the Comoros during 1997-2000. Revenue and domestic expenditure developments resulted in small overall domestic deficits over much of the period, equivalent of 0.4 percent of GDP in 1998 and declining to 0.2 percent of GDP in both 1999 and 2000. With no source of financing, domestic or external, the Anjouan authorities accumulated substantial wage arrears, estimated at about 15 months at end-2000, as well as suppliers arrears.